2018
DOI: 10.1074/mcp.tir118.000740
|View full text |Cite
|
Sign up to set email alerts
|

Endoglycosidase S Enables a Highly Simplified Clinical Chemistry Procedure for Direct Assessment of Serum IgG Undergalactosylation in Chronic Inflammatory Disease

Abstract: Over the past 30 years, it has been firmly established that a wide spectrum of (autoimmune) diseases such as rheumatoid arthritis, Crohn's and lupus, but also other pathologies like alcoholic and non-alcoholic steatohepatitis (ASH and NASH) are driven by chronic inflammation and are hallmarked by a reduced level of serum IgG galactosylation. IgG (under)galactosylation is a promising biomarker to assess disease severity, and monitor and adjust therapy. However, this biomarker has not been implemented in routine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Certain glycoproteins accumulate in the circulation of patients with liver diseases. 113 Liver disease is an attractive field for the study of the serum glycome because most N-glycans found in whole serum are attached to serum proteins produced in the liver 21 and to a lesser extent to Igs, 20,70,114 which are produced by B cells. Alterations in serum glycan structures have been reported in patients with liver diseases 20,22,90,92,114,115,116 (Figure 4).…”
Section: Diagnostic and Prognostic Markers Of Liver Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Certain glycoproteins accumulate in the circulation of patients with liver diseases. 113 Liver disease is an attractive field for the study of the serum glycome because most N-glycans found in whole serum are attached to serum proteins produced in the liver 21 and to a lesser extent to Igs, 20,70,114 which are produced by B cells. Alterations in serum glycan structures have been reported in patients with liver diseases 20,22,90,92,114,115,116 (Figure 4).…”
Section: Diagnostic and Prognostic Markers Of Liver Diseasementioning
confidence: 99%
“…acetylglucosaminidase from Streptococcus pyogenes (endoS) has been developed. 114 This should help advance this biomarker toward clinical implementation. The Sweetblot technique, an automated protocol for integrated glycoblotting and mass spectrometry, detects a combination of 3 glycans in serum (2 core fucosylated and 1 nonfucosylated triantennary glycans) and can distinguish patients with NASH from those with only steatosis (area under the curve, 0.83).…”
Section: January 2020mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, potential fucose rearrangement influences the ratios of diagnostic fragment ion(s), further interfering with the assessment of mixtures by tandem MS (Harvey et al, 2002;Chen and Flynn, 2007;Wuhrer et al, 2011). Alternatively, endoglycosidases can be used for glycomic assays (Benicky et al, 2014;Vanderschaeghe et al, 2018). For example, a combination of Endo F2 and Endo F3 has been used to quantify antennary fucosylation on diantennary and triantennary glycans on hemopexin and complement factor H in patients suffering from liver diseases (Benicky et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These assays are often complicated by the composition and linkage diversity of the glycans and hence they rely heavily on high-end analytical instrumentation [ 17 19 ]. The IgG glycome especially, has been widely studied using assays based on the modern iterations of liquid chromatography (LC) with fluorescence detection (FLD) [ 1 , 20 , 21 ], capillary gel electrophoresis (CGE) with laser-induced fluorescence (LIF) detection [ 22 , 23 ] and matrix assisted laser desorption mass spectrometry (MALDI-MS) [ 24 , 25 ]. These analytical platforms have demonstrated a multitude of times the ability to perform detailed and high-throughput analyses of IgG glycosylation, and have deeply progressed our understanding of the IgG glycome.…”
Section: Introductionmentioning
confidence: 99%